Polymer-metal powders melt extrusion printing to produce high-density, high-conductivity pure copper components - Xiuhu Guo; Junnan Liu; Lu Li; Xiaoying Cui; Muhammad Dilawer Hayat; Peng Cao; Zhentao Yuan; Xiao Wang; Xiulin Chen (Journal of Materials Research and Technology)
In this study, we utilized material extrusion (MEX) molding additive manufacturing and debinding sintering technology to create pure copper parts with high density and exceptional conductivity. This was achieved using self-developed MEX raw materials with pure copper powder accounting for 60 vol %. The macroscopic and microscopic characteristics of green, debound and sintered parts were comprehensively characterized. The relationship between density and different sizes of nozzles and different layer heights was examined. After immersing the green body in an n-hexane solution at 40 °C for 12 h, a debinding rate of 95 % was achieved. The debounded parts were then sintered at 1050 °C in argon-hydrogen (H∼10 vol %) mixed gas. The results show that the copper parts produced with a 0.6 mm nozzle and 0.1 mm layer height exhibited the best performance, achieving a density greater than 98 %, conductivity of ∼93 % IACS, ultimate tensile strength of 198 MPa, and elongation at break of 34 %. This study offers a novel MEX printing approach for the additive manufacturing of pure copper, focusing on raw material formulation and optimizing experimental parameters.